An accessible testing, learning and assessment system for people with intellectual disability. (2nd October 2017) - Davies, Daniel K.; Stock, Steven E.; King, Larry; Wehmeyer, Michael L.; Shogren, Karrie A.
Abstract : Students and adults with intellectual disability experience multiple barriers to taking tests, assessments, evaluations, questionnaires, and surveys. The literacy demands of common formats for soliciting objective and subjective feedback — particularly written questions and answers — makes typical assessment processes inaccessible to many people with intellectual disability. Alternative approaches are time-consuming, often foster dependency on others, and do not provide opportunities or experiences in self-direction. This manuscript reports a pilot test of the use of a cognitively accessible self-paced testing system for students and adults with intellectual disability. The study employed a standard two-group within-subjects design in which 40 participants with intellectual and developmental disabilities completed assessments using both written and computer-based versions of each of the two surveys designed for use in the study. Results suggested that participants were able to complete a typical assessment with greater accuracy, increased independence, and greater efficiency when using the cognitively accessible computer-based survey compared to traditional written test methods.